2021
DOI: 10.48550/arxiv.2109.03114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep learning for the modeling and inverse design of radiative heat transfer

Juan José García-Esteban,
Jorge Bravo-Abad,
Juan Carlos Cuevas

Abstract: Deep learning is having a tremendous impact in many areas of computer science and engineering. Motivated by this success, deep neural networks are attracting an increasing attention in many other disciplines, including physical sciences. In this work, we show that artificial neural networks can be successfully used in the theoretical modeling and analysis of a variety of radiative heat transfer phenomena and devices. By using a set of custom-designed numerical methods able to efficiently generate the required … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…In another application, Liu et al [40] implemented an ensemble of convolutional neural networks (CNNs) to generate optimal surface patterns for structured metasurfaces, where the input to the network was a desired spectral transmittance distribution. Lastly, Garcia et al [41] demonstrated how deep learning techniques can be implemented for the modeling and inverse design of radiative heat transfer phenomena in various systems including hyperbolic metamaterials, passive radiative cooling in photonic-crystals, and emissive power of subwavelength objects.…”
Section: Introductionmentioning
confidence: 99%
“…In another application, Liu et al [40] implemented an ensemble of convolutional neural networks (CNNs) to generate optimal surface patterns for structured metasurfaces, where the input to the network was a desired spectral transmittance distribution. Lastly, Garcia et al [41] demonstrated how deep learning techniques can be implemented for the modeling and inverse design of radiative heat transfer phenomena in various systems including hyperbolic metamaterials, passive radiative cooling in photonic-crystals, and emissive power of subwavelength objects.…”
Section: Introductionmentioning
confidence: 99%